(untitled) - Nguyen, Thi Quynh Hoa (Can Tho, 2010)
The purpose of this research is to study types of "consigne" in " la méthode STUDO 100" through exercises of written expressions on students of English who study French as second foreign language in colledge of pedagogy of Can Tho
Keywords: Second language acquisition,Tiếp thu ngôn ngữ thứ hai,French language,Tiếng Pháp; Study and teaching,Vietnamese speakers,Dạy và học,Người nói tiếng Việt